Translating feminist literature and transformations of gender discourse between two languages: ترجمة الأدب النسوي وتحولات الخطاب الجندري بين لغتين - Zerrad , Djanette (Maalim, 2026)
Feminist literature occupies a distinctive position within contemporary literary discourse, as a mode of writing that articulates female subjectivity through language and reconstructs its relationship with the body, memory, and power. Within this literary practice, narrative and discursive patterns emerge that invest language with explicit gendered dimensions, rendering linguistic choice a constitutive element of identity representation and meaning-making. As this literature moves across languages, translation becomes a space in which feminist discourse is rearticulated within a new linguistic and cultural framework. In this context, translated Arab feminist writing reveals significant transformations in gendered discourse as it circulates into other languages, reshaping representations of the female body and subjectivity in accordance with different horizons of reception. Likewise, Arabic translations of global feminist texts expose the strategies through which gendered concepts are adapted within the receiving language. Through these intersecting trajectories, translated feminist literature emerges as a dynamic discourse shaped by translational choices and the cultural negotiations surrounding gender representation.